2014
DOI: 10.1016/j.eurpsy.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Daily life impairments associated with self-reported childhood/adolescent attention-deficit/hyperactivity disorder and experiences of diagnosis and treatment: Results from the European Lifetime Impairment Survey

Abstract: The Lifetime Impairment Survey assessed impairment and symptoms of attention-deficit/hyperactivity disorder (ADHD) in children/adolescents from six European countries. Parents/caregivers of children/adolescents aged<20 years with ADHD (ADHD group; n = 535) and without ADHD (control group; n=424) participated in an online survey. History of ADHD diagnosis was self-reported. ADHD and control groups were compared using impairment and symptom scales; higher scores indicate greater impairment. Mean (SD) age at ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
1
26
0
1
Order By: Relevance
“…These changes were required despite the child/adolescent being on medication in more than half of cases (53%), suggesting that there may still be unmet needs in the management of ADHD. Our findings are broadly in line with previous research showing the negative effect of ADHD on children/adolescents and their families, although differing study designs prevent direct comparison of data (Caci et al, 2014;Coghill et al, 2008;Kvist et al, 2013;Le et al, 2013;Noe and Hankin, 2001).…”
Section: Characteristicsupporting
confidence: 93%
“…These changes were required despite the child/adolescent being on medication in more than half of cases (53%), suggesting that there may still be unmet needs in the management of ADHD. Our findings are broadly in line with previous research showing the negative effect of ADHD on children/adolescents and their families, although differing study designs prevent direct comparison of data (Caci et al, 2014;Coghill et al, 2008;Kvist et al, 2013;Le et al, 2013;Noe and Hankin, 2001).…”
Section: Characteristicsupporting
confidence: 93%
“…Firstly, we did not address the association of hyperfocusing with some factors like cognitive functions (verbal fluency, set shifting, Stroop interference, response inhibition etc.) and daily functioning that are impaired in ADHD (Boonstra, Oosterlaan, Sergeant, & Buitelaar, 2005;Caci et al, 2014). For example, Kalanthroff et al, (2013) suggested a possible association between deficiency of global processing and social dysfunction in adult patients with ADHD.…”
Section: Resultsmentioning
confidence: 99%
“…ADHD impacts multiple facets of children's lives; school, home, friendships and relationships. Children with ADHD are exposed to higher levels of criticism and hostility in these environments, commonly contributing to lower self-esteem, self-efficacy and self-belief (Caci et al 2014). Children with ADHD are less likely to experience success in academic, extracurricular and other settings such as sport, which often has a profoundly demotivating impact; children who have never fulfilled their true potential and have rarely experienced success may fail to see the value of persistence, effort and application.…”
Section: Early Interventionmentioning
confidence: 99%